The Leadership Styles of Schools Principals and Their Effect in the Organizational Commitment of Teachers: A field study on Kuwaiti Public Schools - Alghadhouri, Hanan Mohammed (Journal of Educational and Psychological Sciences, 2020)
The current study aimed at identifying the Leadership Styles of Schools Principals and Their Effect in the Organizational Commitment of Teachers in Kuwait public schools.The researcher has applied the Relational Descriptive Approach because it suits the objectives of the current study, and the study tool consisted of a questionnaire fir data collection.The sample of the current study consisted of 383)) teachers from Kuwaiti public schools. The study found that the Leadership Styles of Schools Principals in Kuwaiti public schools were of medium-level, as they scored a mean of (3.62 out of 5.00.)At the level of the axis of styles, the democratic style has ranked first with a mean of 3.98)). The easy principal has ranked second with a mean of 3.70)), and these two styles were of a high level. The autocratic style has ranked third with a mean of 3.19) ) which is of medium level.The results of the study showed that the organizational commitment has scored a mean of (3.85 out of 5.00  )with a high level. The results showed that there was a statistically significant effect at the level of significance (α≤0.05) of the degree of the Leadership Styles of Schools Principals and Their Effect in the Organizational Commitment of Teachers which amounted 94.8%)), which means that it is (high and strong). The study recommended increasing the awareness of school principals about of Leadership Styles, and how to apply and exercise them within the educational institution.
Keywords: The impact of leadership styles; Schools Principals; Organizational Commitment; Teachers; Kuwaiti Public Schools